An ecological study exploring the geospatial associations between socioeconomic deprivation and fire-related dwelling casualties in the England (2010–2019). (July 2022) - Li, Lan; Musah, Anwar; Thomas, Matthew G.; Kostkova, Patty
Abstract: Dwelling fires are attributable to the high public health burden of injury and mortality in England. The statistic shows that from 2010 to 2019, over 5, 000 injuries and 200 deaths annually are caused by dwelling fires which accounts for around three-fourths of the total fire-related casualties. Therefore, it is necessary to explore the social risk factors of fire-related dwelling casualties (SCR) and identify high-risk areas in England. In this study, an ecological study design within a longitudinal framework was adopted using a spatial-temporal Bayesian regression model to determine the overall association between the Index for Multiple Deprivation (IMD) and SCR, as well as mapping the relative risk of SCR for 2019 and then predicting the trajectories and levels of sustained risk of SCRs throughout the areas in England across 2010 to 2019. The adjusted risk map shows large variability in the IMD's impacts on dwelling fire casualty risk and the significantly increased risk clustering in the North West and northern parts of the West Midland region, where the risk increases 26%–83%. The results provide an up-to-date picture and facilitate a deeper understanding of social influences on the distribution of dwelling fire risks in England. Highlights: The dwelling fire casualty risk in England has a clear temporal and spatial pattern over the last decade (2010–2019). The association between the socioeconomic variables measured by the IMD and SCR is significant. The domain of living environment and education measured by the IMD are the predominant factors. Risk map shows that FSAs around Lancashire, Merseyside, Manchester, and West Yorkshire exhibits the highest increased risks.